Analisis dan optimasi struktur sasis bus dengan batasan tegangan maksimum dan defleksi pada beban maksimum - Ojo Kurdi; Ismoyo Haryanto; Agus Suprihanto; Ian Yulianti; Nur Aziyah (Jurnal Teknik Mesin Indonesia, 2019)
Chassis is an important part of a vehicle, which forms the frame of a vehicle. Chassis must be rigid enough to withstand shock, twist, vibration and other stresses. An important consideration in chassis design is having adequate bending stiffness along with strength for better handling characteristics. Therefore the maximum stress, and deflection are important criteria for chassis design. The purpose of this study is to determine the most optimum design of the three chassis designs of type C, I and Rectangular Box (Hollow). Get the minimum chassis thickness in the Rectangular Box (Hollow) type bus chassis from the ASO and MOGA optimization methods. And comparing the results of the optimization obtained from the two optimization methods. In this study, two types of software were used, namely CAD software (SOLIDWORKS 2015) for the manufacture of bus chassis models and Finite Element Analysis software (ANSYS Workbench v.16) to simulate structural static loading and optimization. The results of this study indicate that the maximum stress occurs in the cross section C with a stress of 73.235 Mpa, and a deflection of 1.5455 mm. The results of the static load analysis show that the design of the type Rectangular Box (Hollow) is far more optimal than type C or I. Based on the optimization on the Rectangular Box (Hollow) type bus chassis with the two methods, the best results use the ASO method with an optimum mass value of 682, 57 kg (mass reduction percentage of 1.224%) with equivalent (von-misses) stress of 53.557 MPa and total deformation of 1.1847 mm. While the results of the optimization of the MOGA method, the optimization mass value of 686.83 kg with equivalent (von-misses) stress of 53.517 MPa and the total deformation was 1.1809 mm. There was a decrease in mass of 0.608%.